Price, Promotion, and Product Quality: Their Influence on Customer Satisfaction (Case Study of ‘Mie Gacoan’ in Bekasi) - Marlinda, Marlinda; Purnamasari, Pupung (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This study aims to determine how the influence of Price, Promotion, and Product Quality affects customer satisfaction in the case study of Mie Gacoan in Bekasi. Using quantitative methods, data from this study were collected from 100 respondents. using the Likert scale model assessment as the measurement model, which is filled in by the respondent on the questionnaire to be distributed. The preparation of the questionnaire uses a Likert scale, a scale used to measure the attitudes, opinions, and perceptions of a person or group of people about social phenomena with the help of SmartPLS 4 software as a tool for analysis. The results of this study indicate that the Price variable (X1) has a significant effect on Customer Satisfaction (Y) the t-statistic result for the Price variable is 4.913 and is declared significant because the t-statistic value > 1.66 (4.913 > 1.66). Promotion (X2) variables have a significant effect on customer satisfaction (Y), t-statistic > 1.66 (5,287 > 1.66). Product Quality (X3) variables have a significant effect on customer satisfaction (Y), t-statistic > 1.66 (3,258 > 1.66). variable Price (X1). Promotion (X2), Product Quality (X3) has a significant effect on Customer Satisfaction (Y), the F-statistic for the Price, Promotion, Product Quality variable is 195.109 and is declared significant because the F-statistic value > 2.70 (195.109 > 2.70).